Tindak Tutur Ilokusi tentang Penyalahgunaan Agama di Kanal Youtube Raymond Chin - Rani Febriolla De Lima; Maulani Apriliani; Mahkota Teja Kusuma; Natalia Kartika Saputri; Muhammad Isky Yanuar Najib; Asep Purwo Yudi Utomo; Riyadi Widhiyanto; Dwiana Asih Wiranti (CV. Alim's Publishing, 2026)
This study aims to examine illocutionary speech acts used in the context of religious abuse. This problem is examined in pragmatics, specifically through illocutionary speech acts. This study aims to identify and describe the types of illocutionary speech acts in the context of religious abuse in digital media. This study uses a qualitative descriptive approach with a pragmatic theoretical approach. Data were obtained through the listening-and-note-taking method from the video series ESCAPE